SOCIAL STRATIFICATION OF FISHING COMMUNITIES IN SEI BEROMBANG PANAI HILIR SUB-DISTRICT LABUHAN BATU REGENCY NORT SUMATERA PROVINCE - Valian Rahmad Aw Lubis; Kusai Kusai; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in November 2019, which is located in Sei Berombang, Panai Hilir Sub-District, Labuhan Batu Regency, North Sumatra Province. The purpose of this study is to determine the form of social stratification based on honor, wealth, power and education and to know the factors forming social stratification of the fishing community in Sei Berombang. The method used is a survey method with a qualitative approach with the determination of informants using purposive sampling techniques.In the process of forming the social stratification of the fishing community in Sei Berombang based on honor, wealth, power and education, which causes differences in classes between the people namely the upper classes, middle classes and lower classes. The upper classes are people who have honor, wealth, power and high education. At the lower level are people who have low honor, wealth, power and education. While in the middle layer are people who are in the middle layer between the upper and lower layers. There are five factors forming social stratification of the fishing community in Sei Berombang, namely: 1) Social Interaction; 2) Economy; 3) Population growth; 4) Science (Education); and 5) Conflict.Keywords: Social Stratification, Formation of Stratification, Fishing Communi